Using the analytical calculation method for cooling systems studying - Slabospitsky, R.P.; Khazhmuradov, M.A.; Lukyanova, V.P.; Prokhorets, S.I. (Вопросы атомной науки и техники, 2013)
An analytical method for calculating the air flow battery cooling with non-uniform heat distribution in the battery cells is considered. The calculations were done for different air rates and directions. It is shown that to ensure the normal battery operation the air flow rates must be greater than 2 m/s. Приведено аналiтичний метод розрахунку систем охолоджування акумуляторних батарей потоком повiтря при нерiвномiрному розподiлi тепла в чарунках батареї. Розрахунки проведенi для рiзних швидкостей i напрямiв подачi повiтря. Показано, що забезпечити нормальну роботу батареї можна тiльки при швидкостях потоку повiтря бiльше 2 м/с. Приведен аналитический метод расчета систем охлаждения аккумуляторных батарей потоком воздуха при неравномерном распределении тепла в ячейках батареи. Расчеты проведены для различных скоростей и направлений подачи воздуха. Показано, что обеспечить нормальную работу батареи можно только при скоростях потока воздуха больше 2 м/с.